Peningkatan Hasil Pembelajaran Pendidikan Agama Buddha Materi Penghormatan Melalui Penggunaan Audio Visual Berbasis Kontekstual - Sidartha Adi Gautama; Dwi Yulianti; Taridi Taridi (JURNAL INOVATIF ILMU PENDIDIKAN, 2019)
This study aims are to: 1) Describe the conditions and potential of learning using contextual-based audio-visual teaching materials. 2) Produce contextual based audio visual teaching material products. 3) Analyze effectiveness and attractiveness to improve student learning outcomes in the learning process after using contextually-based audio-visual teaching materials in learning Buddhist education. This study uses the research and development approach of Bord and Gall. The study was conducted at SD Tunas Mekar Indonesia Bandar Lampung. Observation instrument data collection techniques, then data were analyzed quantitatively and qualitatively. Based on observational research and the development of contextual-based audio-visual teaching materials it is very supportive and possible to do contextual learning based on 0.67 and product attractiveness has a success rate of 82%. Audio visual teaching materials are able to increase the value of the material Anjali from 66.6 become 88. While in the material Namaskhara there is a change in the value before using the product that developed the average value of students 69.6 become 83,and in the Uttana material the average value of students also experienced significant changes from68.4 to 90. This value is a very meaningful value for improving student learning outcomes so that context-based audio-visual teaching material has been proven to improve learning outcomes in material ways of giving respect in Buddhism in class I SD Tunas Mekar Indonesia Bandar Lampung.Keywords: audio-visual, contextual teaching material, Buddhist education DOI: http://dx.doi.org/10.23960/jiip.v1i2.18182